SURVEI TINGKAT KEPUASAN SISWA KELAS X TERHADAP PEMBELAJARAN PAI SECARA TATAP MUKA TERBATAS DAN TATAP MUKA PENUH DI SMK N 3 PAYAKUMBUH - Vanny Elvionita; Arifmiboy Arifmiboy; Iswantir M; Salmiwati Salmiwati (KOLONI, 2022)
This research is motivated by differences in the satisfaction of class X students with limited face-to-face learning of PAI and full face-to-face at SMK N 3 Payakumbuh, some say they are quite satisfied with limited face-to-face learning and some say they are not satisfied. There are those who say they are satisfied with the full face-to-face learning that has been carried out after limited face-to-face learning and there are also those who want to return to limited face-to-face learning because they feel that limited face-to-face learning is more fun. The objectives to be achieved in this study are to determine the level of student satisfaction with limited face-to-face PAI learning and full face-to-face learning as well as differences in the level of satisfaction of class X students with limited face-to-face PAI learning and full face-to-face learning. This research has a quantitative paradigm using survey research methods to find out about student satisfaction with limited face-to-face and full face-to-face PAI learning. The population in this study were 573 students of class X with a sample of 115 students. Samples were taken using random sampling technique. The data was processed using a simple statistical test assisted by Statistical Product and Service Solutions (SPSS) version 22. Based on the research that the author has carried out at SMK N 3 Payakumbuh, it is known that the results of hypothesis testing indicate differences in satisfaction with limited face-to-face PAI learning and face-to-face learning. face full of sig value. 0.000 < value of that is 0.05. The data on the percentage of the satisfaction level of class X students with face-to-face PAI learning is limited, namely 36% in the low category and the total percentage of the satisfaction level of class X students with full face-to-face PAI learning is 44% in the medium category, which means that students are more satisfied with learning. Full face-to-face PAI compared to face-to-face PAI learning is limited.  Keyword: Student Satisfaction, PAI Learning, Full Face-to-Face, Limited Face-to-face